2006
DOI: 10.1007/s10459-005-5290-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Two Types of Formative Assessment in Predicting Performance of First-year Medical Students

Abstract: Formative assessments are systematically designed instructional interventions to assess and provide feedback on students' strengths and weaknesses in the course of teaching and learning. Despite their known benefits to student attitudes and learning, medical school curricula have been slow to integrate such assessments into the curriculum. This study investigates how performance on two different modes of formative assessment relate to each other and to performance on summative assessments in an integrated, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
68
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 31 publications
11
68
0
4
Order By: Relevance
“…It has been demonstrated that mean formative quiz performance can have a significant, positive correlation to summative examination performance (Dobson, 2008;Poljicanin et al, 2009;Kibble et al, 2011;Lee et al, 2012;Marden et al, 2013). Moreover, Krasne et al (2006) observed that formative assessments that provoked higher order learning, such as the integration and application of knowledge, were more predictive of summative examination performance when compared to formative assessments of lower levels of learning (factual recall, image recognition). Finally, Marden et al (2013) reported that students who performed poorly in formative quizzes were more likely to fail the summative examination, which suggests that formative assessment may be useful in identifying, at an early stage, students that may require additional assistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that mean formative quiz performance can have a significant, positive correlation to summative examination performance (Dobson, 2008;Poljicanin et al, 2009;Kibble et al, 2011;Lee et al, 2012;Marden et al, 2013). Moreover, Krasne et al (2006) observed that formative assessments that provoked higher order learning, such as the integration and application of knowledge, were more predictive of summative examination performance when compared to formative assessments of lower levels of learning (factual recall, image recognition). Finally, Marden et al (2013) reported that students who performed poorly in formative quizzes were more likely to fail the summative examination, which suggests that formative assessment may be useful in identifying, at an early stage, students that may require additional assistance.…”
Section: Introductionmentioning
confidence: 99%
“…Isso acontecia por intermédio de trabalho em grupo, divisão de tarefas em busca de evidências, discussão em pequenos grupos. Em avaliações somativas análogas, pode-se predizer o desempenho discente a partir da nota no exame formativo 14 .…”
Section: Resultsunclassified
“…Adaptive e-learning described in this study provides, through technology, instructional content that adapts to learners' needs or desires [21]. It has the ability to provide the learner with adaptive feedback via numerous pathways that can be immediate and can target a learner's specific action and As recorded in the literature [22], formative activities that provide timely feedback and an opportunity for repetition of core knowledge and fundamental skills with clinical application are good predictors for improved performance in summative assessments and final grades. Our results demonstrated that a significant improvement in mean grades can be achieved when completing a formative e-learning module to learn and practice before grade assessment.…”
Section: Implications For Learning Practicementioning
confidence: 99%